BCG mediated protection of the lung against experimental SARS-CoV-2 infection - Hilligan, Kerry L.; Namasivayam, Sivaranjani; Sher, Alan (Frontiers in Immunology, 2023)
The observation of reduced COVID-19 incidence and severity in populations receiving neonatal intradermal BCG vaccination vaccine raised the question of whether BCG can induce non-specific protection against the SARS-CoV-2 (SCV2) virus. Subsequent epidemiologic studies and clinical trials have largely failed to support this hypothesis. Furthermore, in small animal model studies all investigators have failed to observe resistance to viral challenge in response to BCG immunization by the conventional and clinically acceptable intradermal or subcutaneous routes. Nevertheless, BCG administered by the intravenous (IV) route has been shown to strongly protect both hamsters and mice against SCV2 infection and disease. In this Perspective, we review the current data on the effects of BCG vaccination on resistance to COVID-19 as well as summarize recent work in rodent models on the mechanisms by which IV administered BCG promotes resistance to the virus and discuss the translational implications of these findings.